2011
DOI: 10.1590/s0100-736x2011000600009
|View full text |Cite
|
Sign up to set email alerts
|

Rectal stenosis in pigs associated with Salmonella Typhimurium and porcine circovirus type 2 (PCV2) infection

Abstract: Rectal stricture is an acquired annular fibrous constriction of the rectum that results from a variety of chronic necrotizing enteric diseases. In pigs, it is in most cases a sequel of Salmonella infection. Porcine circovirus type 2 (PCV2) is a known pathogen causing immunosuppression in pigs worldwide. PCV2 infected pigs may be predisposed to salmonellosis. In this report, rectal stenosis was observed in 160 pigs from a herd that experienced an outbreak of enteric salmonellosis over a 4-month period. Distensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(21 reference statements)
1
1
0
1
Order By: Relevance
“…This nonproper submission of material for diagnosis is not restricted to cases of salmonellosis and is frequently observed in many veterinary diagnostic laboratories (Lucena et al 2010, Souza et al 2015. The use of IHC for the diagnosis of salmonellosis is described in sheep (Dagleish et al 2010), horses (Juffo et al 2017), swine (Watanabe et al 2011), turkeys (Beyaz et al 2010) and cattle (Pecoraro et al 2017, Costa et al 2018. In all analyzed materials in the present study, there was positive immunoreactivity in the liver and lung.…”
Section: Discussionsupporting
confidence: 50%
“…This nonproper submission of material for diagnosis is not restricted to cases of salmonellosis and is frequently observed in many veterinary diagnostic laboratories (Lucena et al 2010, Souza et al 2015. The use of IHC for the diagnosis of salmonellosis is described in sheep (Dagleish et al 2010), horses (Juffo et al 2017), swine (Watanabe et al 2011), turkeys (Beyaz et al 2010) and cattle (Pecoraro et al 2017, Costa et al 2018. In all analyzed materials in the present study, there was positive immunoreactivity in the liver and lung.…”
Section: Discussionsupporting
confidence: 50%
“…Assim esse dado é pouco relevante para o diagnóstico das principais doenças na espécie e foi obtido nesse estudo somente para caracterização do rebanho local. Prolapso de reto (observado em um caso) e estenose retal (apesar de ambos estarem ligadas comumente a infecções bacterianas) (Watanabe et al 2011), síndrome dos membros abertos (observada em quatro casos) e uma grande quantidade de malformações (observadas em 11 casos) são descritas como doenças de possível caráter genético (Sobestiansky et al 2012b), porém nem sempre ligadas a uma raça específica. Mioclonia congênita (raças Landrace e Wessex) (Oliveira 2012a) e rim cístico/hidronefrose, condição extremamente vista em abatedouros (Grist 2007), são descritos como genéticos ligados a raças específicas.…”
Section: Resultsunclassified
“…Some of these are Porcine parvovirus [ 125 ], Porcine reproductive and respiratory syndrome virus [ 126 ], Swine Hepatitis E virus [ 127 ], Swine influenza virus , Mycoplasma hyopneumoniae [ 128 ], E. coli [ 129 ], and Salmonella spp. [ 130 ]. A retrospective study of PCV2-infected swine samples has shown that PRRSV was the most frequent coinfecting pathogen (51.9%), followed by M. hyopneumoniae (35.5%), bacterial septicemia pathogens (14%), bacterial pneumonia pathogens (7.6%), and SIV (5.4%) [ 131 ].…”
Section: Factors Associated With Clinical Manifestation Of Pcv-associ...mentioning
confidence: 99%